2020
DOI: 10.1111/dmcn.14739
|View full text |Cite
|
Sign up to set email alerts
|

Predictive validity of the Hand Assessment for Infants in infants at risk of unilateral cerebral palsy

Abstract: Aim To evaluate the sensitivity, specificity, and predictive value of the Hand Assessment for Infants (HAI) in identifying infants at risk of being diagnosed with unilateral cerebral palsy (CP), and to determine cut‐off values for this purpose. Method A convenience sample of 203 infants (106 females, 97 males) was assessed by the HAI at 3, 6, 9, and 12 months. Sensitivity, specificity, predictive values, and likelihood ratios were calculated using receiver operating characteristic curve analysis. Cut‐off value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
(73 reference statements)
0
9
0
Order By: Relevance
“…Our results are in line with those of Ryll and colleagues, who recently reported that prediction of unilateral CP in infants with a specific high risk for unilateral CP on the basis of arm-hand activities can be reliably done from 3.5-4.5 months CA onwards, and that its diagnostic accuracy increases with increasing age. 32 Muscle tone impairment in the lower extremities during infancy did not predict CP; only at the age of the diagnosis of CP hypertonia in the ankles was significantly associated with CP.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 89%
“…Our results are in line with those of Ryll and colleagues, who recently reported that prediction of unilateral CP in infants with a specific high risk for unilateral CP on the basis of arm-hand activities can be reliably done from 3.5-4.5 months CA onwards, and that its diagnostic accuracy increases with increasing age. 32 Muscle tone impairment in the lower extremities during infancy did not predict CP; only at the age of the diagnosis of CP hypertonia in the ankles was significantly associated with CP.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 89%
“…Inclusion of the infants was based on outcomes of cerebral imaging studies and the clinical judgement of the paediatric neurologist. At the time of inclusion, the asymmetry index cut-off values of the HAI [29] were not yet available. Post hoc we could conclude that one child in the EI-UL-MuSSAP scored within the normal range of the HAI and could therefore have been excluded.…”
Section: Discussionmentioning
confidence: 99%
“…An abnormal score on the HAI was defined in two ways: first, as an asymmetry index of at least 9% or a both-hands measure of 44 or lower at 13-14 weeks of age; or second, as an asymmetry index of at least 30% or a both-hands measure of 49 or lower at 15-19 weeks of age. 24 Moreover, a side difference of at least 2 points between the each-hand sum score was considered an aberrant score. 25…”
Section: Methodsmentioning
confidence: 99%